A global health opportunity: The potential of multiplexed diagnostics in low-resource settings - Thor A. Wagner; Courtney A. Gravett; Michael G. Gravett; Craig E. Rubens (Edinburgh University Global Health Society, 2011)
Emerging technology may soon make simultaneous testing for multiple biomarkers feasible in formats applicable to low-resource settings. This creates an exciting opportunity to engineer new diagnostics for a variety of important global conditions.